If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 18 = 6x + 21 Reorder the terms: 18 + 9x = 6x + 21 Reorder the terms: 18 + 9x = 21 + 6x Solving 18 + 9x = 21 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 18 + 9x + -6x = 21 + 6x + -6x Combine like terms: 9x + -6x = 3x 18 + 3x = 21 + 6x + -6x Combine like terms: 6x + -6x = 0 18 + 3x = 21 + 0 18 + 3x = 21 Add '-18' to each side of the equation. 18 + -18 + 3x = 21 + -18 Combine like terms: 18 + -18 = 0 0 + 3x = 21 + -18 3x = 21 + -18 Combine like terms: 21 + -18 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 2p+1=p+3 | | t^2-6t+128=0 | | 2(2)-3=0 | | 6x^2-24x-72=32 | | (4x)(2)=(3x)(243) | | 4+-4p=16 | | 2x-12=x+32 | | 3k=34 | | 6x-10x+4=-2x | | 11r=40-9r | | 5x+1=3x+16 | | x(2-3x)=x^2+7x-4 | | 12x+7=5x+27 | | 6.1=94.55 | | x^2+7+43+2x^2-4=360 | | 7y-7=13y-7 | | 1/1/2=3x | | 3+2-x-1=3x-6 | | 9=-7u+4(u-3) | | 40(15)(-3)/0 | | Xsquared+2x-48= | | 13x+7y=56 | | 3xy+2z=5 | | 2b^2-7b-3=0 | | Fx=12-x/132 | | 25x^2+10x=3 | | k/2-5=-4 | | V/8=-2 | | 10s-s=18 | | b+8b=-18 | | 9a+5b+6a+3b= | | 2x-2=x+32 |